Perbandingan Kapasitas Sambungan Balok -Kolom Konvensional Dan Pracetak Sistem Rigid Joint Precast (RJP) (Studi Kasus Gedung Rumah Susun Sederhana Sewa Pekanbaru) - Arrahman, Feri; Djauhari, Zulfikar; Yuniarto, Enno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Precast system is a system which offers quality controlled implementation, they are neat, fast and economical, thus included systems that fiil the criteria for green construction. Precast concrete construction has many advantages than conventional systems. The advantage of this system are, quality assured, fast and massal production, rapid development, environmentally friendly and tidy with good product quality. For buildings precast system have been researched, developed, applied and proven reliability by the Ministry of Public Works and the various national construction industry since 1995, especially in support of the development program of massal simple flat throughout Indonesia. One of the buildings using precast system is building Rusunawa Pekanbaru. This Rusunawa using RJP-type system of precast concrete. Part of the concern is a precast system on beam-column connections. Beam-column relationship is a critical area in the event of earthquake loads. Earthquake load has a complex effect on the structure. In this study has compared the moment capacity between conventional beam-column connections with precast type of RJP. The results are there differences in the precast concrete RJP peak voltage at the connection angle (A), exterior (B) and interior (C) in the amount of 53.85 MPa, 54.31 MPa and 54.31 MPa. RJP moment the total capacity are equal to A = 140.35 kN.m, B = 116.96 kN.m and C = 116.96 kN.m. Peak voltage difference and the connection moment capacity caused by configuration differences longitudinal reinforcement.Keyword : precast, RJP, conventional, confined, connection